Quantifying TERT promoter mutations in tumor-derived DNA shed into the oral cavity as a potential biomarker for oral squamous cell carcinoma - Starita, Noemy; Tagliabue, Marta; Gheit, Tarik; Cerasuolo, Andrea; Amiranda, Sara; Pecchillo Cimmino, Tiziana; Dassi, Luisa; Tornesello, Anna Lucia; De Berardinis, Rita; Maffini, Fausto; De Palma, Giuseppe; Vecchio, Stefania; et al. (Frontiers in Oncology, 2025)
BackgroundHead and neck squamous cell carcinomas (HNSCC) have high recurrence and poor prognosis, largely due to delayed diagnosis. Identification of somatic mutations and human papillomavirus (HPV) sequences in tumor DNA shed in the oral cavity may provide non-invasive biomarkers for early HNSCC detection.ObjectivesThe study aimed to evaluate TERT promoter (TERTp) mutations in tumor DNA extracted from oral rinses as potential biomarkers for head and neck cancers.MethodsTERTp mutations (C228T and C250T) were examined in DNA extracted from oral rinses of 132 HNSCC patients, of whom 63 had paired tumor tissue available for analysis, and from four head and neck squamous cell carcinoma derived cells lines (CAL27, SCC152, SCC154, FaDu) by using droplet digital PCR (ddPCR). TERT gene expression was analyzed in all cell lines by real time PCR. Associations with tumor site, smoking status, and sex were evaluated, and mutant allele frequencies (MAF) quantified.ResultsTERTp mutations were identified in 25% of oral rinses (33 out of 132, 95%CI 22.7 - 46.3) and in 27% of tumor tissues (17 out of 63, 95%CI 9.9 - 27.2). Mutation rates were highest in oral SCC (OSCC), present in 50% of oral rinses (n=25/50, 95%CI 16.2 - 36.9) and 46% of matched tumor tissues (n=13/28, 95%CI 6.9 - 22.2), with 96% concordance (kappa value 0.86, 95%CI 67-100). MAF were higher in tumor tissues and correlated with levels in corresponding oral fluids. Mutations were uncommon in non-OSCC cases, being detected in 9.7% of oral rinses and 11% of tumor tissues. In OSCC, TERTp mutations were more frequent in males. The CAL27 cell line carried the TERTp C228T mutation and TERT mRNA expression was 11–15 folds higher compared to non-mutated oral carcinoma cell lines.ConclusionsTERTp C228T and C250T are mutually exclusive and occur at a high frequency in oral rinses and tumor tissues of OSCC patients, showing high concordance between paired samples. These findings support the potential of TERTp mutations as non-invasive biomarkers for OSCC detection. Moreover, their higher prevalence in males suggests possible sex-related differences in OSCC mutation patterns.